Siva 1 inhibits proliferation, migration and invasion by phosphorylating Stathmin in ovarian cancer cells - Ma, Yifei (Oncol Lett, 2017)
Ovarian cancer is one of the most common types of gynecologic malignant tumor, with high incidence and high mortality rates. It is difficult to diagnose ovarian cancer early due to the complex structure and function of the ovaries. Siva 1 is a well-known pro-apoptosis protein that functions in multiple types of cancer cells: There are several studies demonstrating that Siva 1 arrests apoptosis and facilitates cancer development in osteosarcoma and non-small cell lung cancer. Whether Siva 1 functions in ovarian cancer remains unknown. In the present study, it was established that Siva 1 was stably overexpressed in ovarian cancer cell lines, and demonstrated that the overexpression of Siva 1 inhibited proliferation, promoted apoptosis and suppressed migration and invasion by facilitating phosphorylation of Stathmin and polymerization of α-tubulin in ovarian cancer cells. These data provide specific novel insights into the molecular mechanism of ovarian cancer, and may be of significance for the clinical diagnosis and therapy of ovarian cancer.